Biochemical and conformational characterisation of HSP-3, a stallion seminal plasma protein of the cysteine-rich secretory protein (CRISP) family. - Schambony, Alexandra; et al. (FEBS letters, 1997)
HSP-3 is a member of the cysteine-rich secretory protein (CRISP) family from stallion seminal plasma. We report a large-scale purification protocol for native HSP-3. This protein is a non-glycosylated polypeptide chain with a pI of 8-9 and an isotope-averaged molecular mass of 24987 +/- 3 Da. The molecular mass of HSP-3, determined by equilibrium sedimentation, is 26 kDa, showing that the protein exists in solution as a monomer. The concentration of HSP-3 in the seminal plasma of different stallions ranged from 0.3 to 1.3 mg/ml. On average, 0.9-9 million HSP-3 molecules/cell coat the postacrosomal and mid-piece regions of an ejaculated, washed stallion spermatozoon, suggesting a role in sperm physiology. Conformational characterisation of purified HSP-3 was assessed by combination of circular dichroism and Fourier-transform infrared spectroscopies and differential scanning microcalorimetry. Based on secondary structure assignment, HSP-3 may belong to the alpha+beta class of proteins. Thermal denaturation of HSP-3 is irreversible and follows a non-two state transition characterised by a Tm of 64 degrees C, an enthalpy change of 75 kcal/mol, and a van 't Hoff enthalpy of 184 kcal/mol. Analysis of the spectroscopic and calorimetric data indicates the occurrence of aggregation of denatured HSP-3 molecules and suggests the monomer as the cooperative unfolding unit.